Penerapan Penilaian Beracuan Patokan dan Norma pada Pelajaran Sejarah Kebudayaan Islam di Madrasah Aliyah Swasta Darul Hadits Huta Baringin - Nurhayani, Nurhayani; Zulhimmah, Zulhimmah; Efendi, Manahan Efendi; Harahap, Hasnah Azhari (CV. Lenggogeni Data Publishing, 2024)
The research method chosen was qualitative, with a descriptive analysis method, because the researcher wanted to analyze based on the teacher's verbal statements from each type of daily test, Mid-Semester Examination (UTS), and Final Semester Examination (UAS). This research aims to describe the results of teacher assessments which are then analyzed and compared with the theory of learning outcomes assessment related to the Benchmark Reference Assessment Approach (PAP) and Norm Reference Assessment (PAN). In the Benchmark Assessment Approach (PAP), teachers are responsible for helping students towards achieving predetermined standards. Students are considered to have graduated if they achieve or exceed the predetermined success criteria. This approach helps teachers design improvement programs and provide consistent feedback to students. On the other hand, the Norm Referenced Assessment Approach (PAN) measures a student's abilities relative to his or her group. PAN considers the normal distribution of students' abilities and places students in certain categories such as